2016
DOI: 10.7863/ultra.15.08052
|View full text |Cite
|
Sign up to set email alerts
|

Early Evaluation of Relative Changes in Tumor Stiffness by Shear Wave Elastography Predicts the Response to Neoadjuvant Chemotherapy in Patients With Breast Cancer

Abstract: Early evaluation of relative changes in tumor stiffness using SWE could effectively predict the response to neoadjuvant chemotherapy in patients with breast cancer and might indicate better therapeutic strategies on a timelier basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 31 publications
1
52
0
1
Order By: Relevance
“…The described method can potentially be useful both as a treatment evaluation tool to probe stiffness of ablated tissue, and as a diagnostic tool to efficiently investigate differences in mechanical properties between, for example, malignant and healthy tissue. 48,49 2 | METHODS…”
Section: Magnetic Resonance In Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…The described method can potentially be useful both as a treatment evaluation tool to probe stiffness of ablated tissue, and as a diagnostic tool to efficiently investigate differences in mechanical properties between, for example, malignant and healthy tissue. 48,49 2 | METHODS…”
Section: Magnetic Resonance In Medicinementioning
confidence: 99%
“…In the porcine brain it is shown that the measured displacement decreases after ablation due to increased tissue stiffness. The described method can potentially be useful both as a treatment evaluation tool to probe stiffness of ablated tissue, and as a diagnostic tool to efficiently investigate differences in mechanical properties between, for example, malignant and healthy tissue …”
Section: Introductionmentioning
confidence: 99%
“…These results could be used for imaging methods such as MRE for in vivo treatment evaluation. In fact, elastography method using ultrasound has been used to assess the relative change of the tumor stiffness to predict the early treatment response to chemotherapy [42]. In addition, unlike the ex vivo testing methods such as TUNEL stain that takes days of work to be fixed, stained, and observed, biomechanical characterization methods provide a potentially more efficient and convenient alternative.…”
Section: Treatment Evaluationsmentioning
confidence: 99%
“…В зарубежной литературе нам встретились лишь 6 работ по оценке эффективности НХТ на основании динамики показателей жесткости первичной опухоли с помощью соноэластографии (СЭГ), и лишь 2 из них посвящены исследованию компрессионной эластогра-фии [20,21], в остальных применялась эластография сдвиговой волны [22][23][24][25][26]. M. Hayashi и соавт.…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified